2020
DOI: 10.1038/s43018-019-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal genomic features predict outcome of immune checkpoint blockade in non-small-cell lung cancer

Abstract: Despite progress in immunotherapy, identifying patients that respond has remained a challenge. Through analysis of wholeexome and targeted sequence data from 5,449 tumors, we found a significant correlation between tumor mutation burden (TMB) and tumor purity, suggesting that low tumor purity tumors are likely to have inaccurate TMB estimates. We developed a new method to estimate a corrected TMB (cTMB) that was adjusted for tumor purity and more accurately predicted outcome to immune checkpoint blockade (ICB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 63 publications
8
153
1
Order By: Relevance
“…Tumors with higher TMB have been hypothesized to have more neoantigens that can be recognized by the immune system in response to checkpoint inhibition, yet the data presented here and data previously published [2] support the use of substantially different "absolute" TMB thresholds for immunotherapy response prediction across different diseases. Further, evidence suggests that other genomic factors, such as tumor purity and clonal heterogeneity, may further modulate the relationship between TMB and immunotherapy response [57,67]. This suggests an added layer of as-of-yet undefined complexity not captured in the current bulk metrics, and likely related to disease-specific biology.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with higher TMB have been hypothesized to have more neoantigens that can be recognized by the immune system in response to checkpoint inhibition, yet the data presented here and data previously published [2] support the use of substantially different "absolute" TMB thresholds for immunotherapy response prediction across different diseases. Further, evidence suggests that other genomic factors, such as tumor purity and clonal heterogeneity, may further modulate the relationship between TMB and immunotherapy response [57,67]. This suggests an added layer of as-of-yet undefined complexity not captured in the current bulk metrics, and likely related to disease-specific biology.…”
Section: Discussionmentioning
confidence: 99%
“…A signi cant contribution of immune cells to LADC has been widely accepted [18],and immune gene was thinked as a biomarker for immune response in immunotherapy [19]. Earlier studies also showed that some immune genes are signi cantly related to the prognosis of LADC [20]. In addition, other studies have found that immune gene expression should be included in the current multi-gene test to improve the prognosis of patients with LADC [21,22].…”
Section: A B 4 Discussionmentioning
confidence: 99%
“…Tumors with higher TMB have been hypothesized to have more neoantigens that can be recognized by the immune system in response to checkpoint inhibition, yet the data presented here and data previously published (2) support the use of substantially different "absolute" TMB thresholds for immunotherapy response prediction across different diseases. Further, evidence suggests that other genomic factors, such as tumor purity and clonal heterogeneity, may further modulate the relationship between TMB and immunotherapy response (62,72) . This suggests an added layer of as-of-yet undefined complexity not captured in the current bulk metrics, and likely related to disease-specific biology.…”
Section: Discussionmentioning
confidence: 99%